PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAAN KERJA SERTA IMPLIKASINYA PADA KINERJA PEGAWAI (Studi pada Perawat Rumah Sakit Permata Hati di Lamongan) - Ria Setiawati; Survival; Irfany Rupiwardani (MANAJEMEN DEWANTARA, 2026)
The success of hospital services is not only reflected in the completeness of medical facilities, but also in the quality of its human resources, particularly nurses. This study aims to examine the effect of leadership and organizational commitment on nurses’ performance, with job satisfaction as a mediating variable. This research employed a quantitative method with an explanatory research approach. The population and sample of this study consisted of 36 nurses, and data were collected through questionnaires. Data analysis was conducted using SEM-PLS version 4.0. The results indicate that leadership and organizational commitment have a positive and significant effect on nurses’ performance. Leadership and organizational commitment also have a positive and significant effect on job satisfaction. Furthermore, job satisfaction mediates the relationship between leadership and organizational commitment and nurses’ performance. The implications of this study show that leadership and organizational commitment play an important role in improving job satisfaction and nurses’ performance. Therefore, hospital management needs to prioritize strengthening leadership quality and creating a supportive work environment to enhance nurses’ performance. Theoretically, these findings confirm the role of job satisfaction as a mediating variable that strengthens the influence of leadership and organizational commitment on nurses’ performance.